(untitled) (Research, Society and Development, 2022)
High Blood Pressure is a disease of extreme recurrence in the brazilian population and presents characteristics that make it an important risk factor for the development of cardiovascular outcomes. In this context, the study of the prescriptive profile of drugs in a given location can identify and assess important variables in prescriptive quality. This study analyzed the profile of prescription of antihypertensive drugs in Primary Care in the town of Araranguá, in Santa Catarina state, according to the perception of prescribers. A cross-sectional, quantitative, descriptive study was carried out through a semi-structured interview, applied between December 2021 and February 2022. The study population consisted of medical prescribers who work in the Primary Care network in the town of Araranguá. The obtained results showed that the profile of the physicians is composed, predominantly, of young professionals (<30 years) and with little clinical experience. The ways of clinical update most used by the prescribers were guidelines/consensus and apps/medical websites. The most prescribed classes of antihypertensives were, in order: Angiotensin-converting Enzyme Inhibitors, Thiazide Diuretics and Angiotensin Recepto agreed that the Unified Health System provides the necessary drugs to treat hypertension. Thus, the profile of prescription of antihypertensive drugs in AB in the town of Araranguá shows certain heterogeneity, but, in general, it is congruent with the best available evidence for the treatment of hypertension.